Green science: Decoding dark photon structure to produce clean energy - Md. Faruque Hossain (Energy Reports, 2018)
To produce energy from dark photon Ú, I have proposed it to collide with Higgs-boson BR(HÇÚÚ) quantum under extreme relativistic condition (ERC). Just because Higgs-boson, BR(HÇÚÚ) quantum get excited at extreme relativistic condition and its quantum field get extreme short-range week force to create electromagnetic field. Thus, I have assumed that the results of electrically charged particles of dark photon Ú (non-energy level photon) into the extreme relativistic condition shall indeed create energy level photon, here named as Hossain Dark Photon (HdP-). To confirm this HdP- transformation by Higgs boson BR(HÇÚÚ) quantum interaction, I have performed series of mathematical modeling by using MATLAB software. Interestingly, the mathematical calculation revealed that the presence of an extra relativistic condition does transform dark photon Ú into HdP- at Neff=4.08−0.68+0.71 at 95% level l.c. (confidence limit) respectively dark photon's speed ceff and viscosity cvis parameters as d ceff=20.312±0.026 and cvis2=-0.16+0.21, consistent with the expectations of a relativistic free streaming componentceff=2cvis2=1∕3. With the presence of Neff, the HdP− photon transformation dynamics was also modeled at nano scale by cavity waveguides circuit considering atomic spectra contour maps of Hamiltonian (H=∑ωciai†ai+∑Kωkbk†bk+∑ikVika†bk+Vik∗bk†ai) embedded in a semiconductor. The result revealed that the transformation of Hossain Dark Photons (HdP-) by Higgs-boson [BR(HÇÚÚ] particle reaction under extreme relativistic condition (ERC) are very much energy level to produce the electricity.
Keywords: 330; Hossain Dark Photon (HdP ); Dark photon; Higgs-boson [BR(HÇYY ] particle; Photo-physics; Renewable energy; Ultra relativistic condition